Uji Validitas Konstruk Resiliensi - Meggy Octaryani; Akhmad Baidun (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
This research aims to measure the construct validity of resilience scale scale developed by Connor dan Davidson (2003). The scale consists of 48 items with five aspects, that is personal competence; trust in one’s instincts; positive acceptance of change and secure relationships; control and factor, spiritual influences. The sample this research is 200 male firefighters in DKI Jakarta and taken using non probability sampling technique.The research data is analyzed using Confirmatory Factor Analysis (CFA) technique with Llisrel 16.0 program. Tujuan dari penelitian ini adalah untuk menguji validitas konstruk skala resiliensi yang dikembangkan oleh Connor dan Davidson (2003). Alat ukur ini terdiri dari 48 item dengan lima aspek, yaitu personal competence; trust in one’s instincts; positive acceptance of change and secure relationships; control and factor dan spiritual influences. Sampel penelitian ini berjumlah 200 orang laki-laki petugas pemadam kebakaran di DKI Jakarta dan diambil dengan menggunakan teknik non probability sampling. Dianalisis menggunakan metode Confirmatory Factor Analysis (CFA) dengan bantuan program Lisrel 16.0.DOI: 10.15408/jp3i.v6i1.8150